Program Aksara dalam Membangun Budaya Literasi di Dusun Nagrog, Desa Kertabumi: Studi Kasus Pemberdayaan Literasi Sejak Usia Dini - Zahra Agustia; Siti Zahara Marwah; Pandu Jaya Laksono; Nirmala Putri; Hazmi Muhammad Rahman; Ikrima Nurhasani; Ahmad Hamdan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This study examines the implementation of a literacy movement program that focuses on fostering early literacy and building a culture of literacy in Nagrog Hamlet, Kertabumi village. The program has shown remarkable effectiveness in increasing children’s interest in reading through situational approaches and fun learning methods. This study shows three main findings: Firstly, the program has successfully increased children’s interest in reading through interactive activities such as shared reading, book coaching and reading aloud. Secondly, the program faces the challenges of limited book collections that match children’s interests and the lack of adequate library facilities in schools. Thirdly, the program succeeded in creating a more inclusive community literacy culture, changing children’s habits from playing with tools to reading and discussing together. This research proves that with the right literacy approach, reading habits can be transformed into social activities that strengthen community relationships.